DENTISTRY OF SLEEP: IMPACTS ON QUALITY OF LIFE (REMUNOM, 2026)
Sleep Dentistry plays an important role in studying the causes and consequences of the relationship between sleep, the oral cavity, and the maxillofacial region of individuals. The aim of this work is to present a critical review of the literature on Sleep Dentistry and demonstrate how it can impact people's quality of life. To achieve this objective, a search was conducted in the Embase, Web of Science, and PubMed databases using the descriptors "dentistry," "sleep," "quality of life," and "Sleep Medicine Specialty." The main articles that were most relevant to the topic of the present study were selected. Many analyzed articles found that sleep and circadian rhythm dysregulation directly influence oral health and weaken the immune system, leading to the onset of dental caries and periodontitis. Additionally, Sleep Bruxism (SB) is one of the disorders that affects quality of life, considered a probable risk factor for Temporomandibular Disorders (TMD), present in 16 to 33% of children. Therefore, it is concluded that quality of life, oral health, and sleep are directly related; however, more research on Sleep Dentistry is needed, as it is still under-discussed by students and professionals. Its inclusion in undergraduate curricula and in the routine of dentists is necessary for effective and clear understanding of this topic.